Dehydrogenation of Ethylbenzene in the Presence of CO2 Over Iron-Chrome Binary Oxide Catalytic System - Aouissi, Ahmed; Bayahia, Hoceine; A. AL-Othman, Zeid; Al-Owais, Ahmed (Asian Journal of Chemistry, 2012)
A series of iron-chrome binary oxide with different ratios were prepared by co-precipitation method and calcination at 750 ºC. The oxides were characterized by means of FTIR, X-ray powder diffraction (XRD) and tested in the dehydrogenation of ethylbenzene in presence of carbon dioxide. The results showed that the main oxide phases forming the binary oxides catalysts were a-Fe2O3 and Cr2O3. Exceptionally, the binary oxides with equal Fe and Cr molar ratio showed modified structural characteristics as compared with the corresponding pure oxides, a-Fe2O3 and Cr2O3. The catalytic tests for dehydrogenation of ethylbenzene with CO2 showed that catalysts with high and low Fe content enhanced the formation of cracking products, whereas those with equal Fe/Cr ratios increased the styrene formation.